MANAGEMENT OF VILLAGE FUNDS (ADD) IN DEVELOPMENT OF EDEN GARDEN IN BAUMATA BARAT VILLAGE KECAMATAN TAEBENU NUSA TENGGARA TIMUR: economic development - usman, hidayah usman (Advances in Social Sciences Research Journal, 2019)
ABSTRAK: Village fund management (ADD) is a right and obligation that is owned by each region, so that it can be used properly to meet development needs. With the village funds being given to be managed properly, West Baumata Village uses a portion of the village's funds to make or build eden parks. This eden park is a program of the Kupang Regent, which requires that every village in Kupang Regency use village funds to build an eden park, aiming for the eden park to become a place of learning for farmers and so that the farming community can benefit from the Eden Garden. The purpose of this study, to analyze how the management of village funds for the development of the Eden park. The research method used was descriptive qualitative, data collection was carried out by observation, direct interviews, and documentation. Data analysis used includes data collection, data reduction, data presentation, and conclusion drawing. The results of the study show that in managing village funds for the construction of the Eden park, the West Baumata Village Government has carried out each of its activities starting from the planning stage, the implementation stage, and the answer stages in accordance with the applicable regulations. Keywords: Management, Village Funds, Garden of Eden